Strategy implementation of prepaid water meters in the city of Johannesburg - Loteni, Nontsikelelo (My University, 2017)
The City of Johannesburg has on several occasions reported challenges that were experienced with regards to revenue collection. It has been acknowledged by the Major of Johannesburg that the billing system is one of the biggest challenges facing by the City of Johannesburg. During the State of the Nation‘s Address President Jacob Zuma announced that the City of Johannesburg will be assisted to resolve the problems with the billing system (State of the Nation‘s Address, 2014). According to The City of Johannesburg‘s annual reports, revenue collection is still problematic. As of 30 June 2016, the nett outstanding consumer debtors amounted to R6.2 billion [2015: R5 billion]. Water debtors account for 31% of the total nett consumers debtors balance. According to The City of Johannesburg‗s annual report the total consumer debtors increased by 24% from the previous year, driven mostly by the prevailing economic conditions. When prepaid water meters were introduced, it was a proactive mechanism to mitigate this problem and provide households with the opportunity to monitor and manage their usage without incurring debts for the service. The researcher is interested in exploring the success of the implementation of prepaid meters and to explore the challenges and lessons learned during the implementation of this intervention. This study will therefore assess whether or not the prepaid water meters can be rolled out to other Regions within The City of Johannesburg. Government has been accused of developing good strategies that promise to change the lives of many South Africans, however, results have shown that the implementation has failed in many government institutions. Municipalities are at the core of ensuring that citizens receive quality service delivery. With the problems that are facing municipalities, especially the issue of payment for services new models and different approaches will be required to ensure that provision of efficient services becomes a reality. Effective strategic implementation has become the critical phase in ensuring that municipalities achieve its objective of providing improved service delivery. This study is based on the views of strategic management theory and reviewed literature on strategic implementation. For the purpose of this study factors were analysed that contribute to the successful implementation of the strategy. These factors include the following: communication of the strategy; involvement of key stakeholders; assignment of responsibilities and putting in place control measures to monitor the implementation progress. These factors are further supported by a discussion of the two key approaches or models to strategy implementation and these are McKinsey 7‘s model, as well as the balance scorecard. Both models provided a guide on the important aspect of the business that needs to be considered when implementing strategy. Managers are also expected to know these factors and take them into consideration, when planning and implementing strategy. The literature review also revealed some of the challenges that could be faced with the implementation of the strategy. Both internal and external factors are equally important in the implementation of the strategy and if not considered properly during the planning stage, they have the potential to contribute largely to the challenges experienced during implementation. This study was conducted using a qualitative study whereby interviews and document analysis were utilised to collect data. The findings revealed that there is still a gap on how the process of strategic management is implemented. A combination of internal factors such as involvement of all stakeholders during the planning and formulation phase, change management and consultation and putting in place control systems were critical to the implementation of the strategy. External factors such as customer involvement, involvement of politicians in driving change, as well as continuous education of society about the intervention were also identified as one of the key factors. The study recommended that an implementation framework be developed which will summarise a comprehensive process of effective strategic implementation. The City of Johannesburg‘s mandate will always be to provide services to its citizens and therefore is possible that the implementation of some projects may take a similar approach. This framework will therefore assist as a guideline for such similar interventions
Research Report submitted to the Faculty of Commerce, Governance and Management, University of the Witwatersrand, in fulfillment of the requirements for the Degree of Masters of Management (In the field of Public Sector Monitoring and Evaluation
Keywords: Water-meters--South Africa; Municipal water supply--Economic aspects--South Africa